Gestão, território e desenvolvimento: dificuldades e perspectivas do município de Tabatinga - SP - Brumatti, Lívia Martinez [UNESP] (2015)
Brazil has been experienced from the 1990s, changes in the organization of its territory. The capitalist production logic, with a financial and international character has been established during this period in the country, causing, among other things, processes of concentration / agglomeration of similar or complementary productive activities in the same municipality or region. It has been occurred, from that period, a large emergence of these productive organization forms (concentrated in agglomeration) in the country. As a result, Brazilian public institutions began to show great interest in them, as ways of promoting development in the territories. In this sense, this work aimed to understand the problems and prospects of the companies in the industrial agglomeration of the municipality of Tabatinga-SP, with an emphasis on financial management of the same, in order to check the conditions of these companies to face an environment of great competition of market. In addition, it sought to identify and analyze the relationships among the companies in the search for their own development and for the development of the territory in which they operate. To this end, it has been performed: theoretical studies on the topics; collection of secondary data to knowledge the branches of stuffed toys and of baby outfits; and field research with nine companies of the agglomeration. It has been identified that, initially, the companies had difficulties related to their informality. To overcome this condition, they worked in the formalization of the companies, the hiring of new employees (already with formal relations) and the changing of domestic location for commercial property, for which, therefore, could promote growth in sales and market share. Interviewed companies have individualized actions (buying, selling and innovation), which could be collective if the industrial agglomeration presented a dynamic cooperation. In addition, there are numerous...